Bridging the Digital Gap: How Soft Skills, Supportive Environments, and Media Usage Drive Teacher Competence in 21st-Century Classrooms - Eko Darmanto; Soni Adiyono (Universitas Pendidikan Ganesha, 2025)
The rapid development of digital technology in the era of Education 4.0 requires teachers to possess strong digital competencies. However, many teachers continue to rely on conventional instructional approaches, resulting in a widening gap between pedagogical capabilities and the demands of digitalized learning. This study aims to analyze, evaluate, and interpret the simultaneous effects of soft skills, environmental support, and digital media utilization on teachers’ digital competence. This research employs a quantitative approach with an associative research design. The study involved 123 teachers selected through purposive sampling as the research sample. Data were collected using standardized questionnaires that had been validated through validity and reliability testing. Data analysis was conducted using Structural Equation Modeling (SEM) to examine both direct and indirect relationships among the variables. The findings indicate that digital media utilization has the strongest influence on enhancing teachers’ digital competence, followed by environmental support, which serves as a key enabling factor. Soft skills do not show a significant direct effect; however, they contribute indirectly when combined with strong environmental support and effective use of digital media. The study concludes that strengthening teachers’ digital competence requires synergy between habitual technology use, institutional support, and personal capacity development. The implications of this study highlight the importance of practice-based training strategies, strengthening digital infrastructure, and fostering a collaborative school culture to build a learning ecosystem that is adaptive to digital transformation.